THE ROLE OF DIGITAL MARKETING TOOLS IN THE ACTIVITIES OF ONLINE STORES (American Journal of Pedagogical and Educational Research, 2023)
The article analyzes the mechanism of interaction between an online store and customers by means of digital marketing. The general features of digital marketing tools in comparison with traditional media are revealed. It is shown that all the tools used by online stores make it possible to work selectively with fairly narrow segments of the audience.